Evolution of attack in handball when playing 7 vs. 6 with empty goal between 2020 and 2023: coaches’ perception vs. observational results - Prudente, João Nunes; Cardoso, Américo Ramos; Rodrigues, Ana José; Mendes, João N.; Fernando, Catarina; Lopes, Helder; Trejo-Silva, Alejandro; Sousa, Duarte Filipe (Frontiers in Sports and Active Living, 2024)
Recently, several studies on the 7 vs. 6 "empty goal" (EG) in handball have produced different and even contradictory results. The aim of this study is to investigate the behavior of teams and players in the 7 vs. 6 EG attack in the European (Euro) and World (WCh) Championships between 2020 and 2023 and characterize the coaches' perception. A mixed methods approach was used: (i) an observational methodology and instrument developed and validated to collect observational data on player and team behavior, and (ii) a developed and validated questionnaire to coaches on their perceptions of the 7 vs. 6 game. Observational data were collected during the Euro2020 and 2022 (n=62 games) and the WCh2021 and 2023 (n=70 games). A total of 132 games and 391 situations of 7 vs. 6 attacking sequences were observed. 156 coaches participated (146 males), age 42.33±11.87 years, 19 nationalities, with 12.77±9.45 years of experience. The choice of 7 vs. 6 offensive play was mostly made in the second half (>73%). The effectiveness of 7 vs. 6 offensive sequences was higher in the top 6 teams than in the team’s ranked 7th to 12th (Euro2020 51.6%-50.0%; WCh2021 52.0%-50.0%; Euro2022 53.1%-41.7%; WCh2023 50.0%-43.8%). Some patterns of association were found (p<0.05 and with values >±1.96): (i) scoring a goal with a breakthrough shot is significantly associated with the effectiveness of the 7 vs. 6 attack (Euro2020-2.61; WCh2021-2.87; Euro2022-2.68; WCh2023-2.32); (ii) teams in the top six significantly use 7 vs. 6 when they were winning (Euro2020-2. 17; WCh2021-3.52; Euro2022-5.88; WCh2023-2.54); and (iii) teams in the bottom six used it when they were losing by at least four goals (Euro2020-7.56; Euro2022-6.64; WCh2023-4.37) or when they were winning by four goals or more (WCh2021-2.58). Coaches that agree with the possibility of playing 7 vs. 6 (74.4%), rarely or never do so (55.6%) because it brings little or no advantage (52.6%). The results of analysis confirm the perception of the coaches, the low use of 7 vs. 6, the low advantage associated with it and the influence of the result and the moment of the game on its use.